Factors that affect the acceptability of plastic straw bans by sari-sari store owners in Iloilo City - Alberto, Erika Suzette; Lisbog, Mary June.; Molina, Ivy.; Napuli, La Pia Paula; Parcia, Jenirose; Parcon, Deza Jane. (2018.)
The study about the acceptability of plastic straw bans by sari-sari store owners in Iloilo City was conducted at four districts of Iloilo City namely City Proper, Jaro La paz and Mandurriao. This study was conducted to find out the level of acceptability of plastic straw bans by sari-sari store owners in Iloilo City and to know what socio-de,ographic and psychographic factors would influence the respondents acceptability. Based on the data gathered through a survey with a total of 144 sari-sari store owners. Mostly of the respondents are composed of female owners aand most of them belong to Generation X. With regards to the significance of factors that affect the acceptability of the sari-sari store owners to Plastic Bans the researchers uses chi-square. And based on the reaults all socio-demographic factors does not have any significant effect on the sari-sari store owners acceptability of plastic straw bans. while with regards to the psychographic factors all factors had a significant effect on the acceptability of sari-sari ownerss except one factor which is disgust. With the results obtained from the study the researchers recommend that if the government will pursue the banning of plastic straws they must first get the opinion of those who will be affected, strictly implement it and must have a good source for the alternatives. And to future researchers who wanted to adapt the same research study, the researchers suggest that they use consumers as their respondents and not mainly focus on sari-sari store owners.
Research Paper (Mgt 199 - Management Research) -- [Iloilo City] : University of the Philippines Visayas - College of Management, December 2018.